Nagwa uses cookies to ensure you get the best experience on our website. Learn more about our Privacy Policy.
Start Practicing

Worksheet: Operations with Complex Numbers in Polar Form

Q1:

Given that 𝑧 = 3 ο€Ό 1 1 πœ‹ 6 + 𝑖 1 1 πœ‹ 6  c o s s i n , find 1 𝑧 in exponential form.

  • A 1 𝑧 = 𝑒 πœ‹ 6 𝑖
  • B 1 𝑧 = 1 3 𝑒 1 1 πœ‹ 6 𝑖
  • C 1 𝑧 = 3 𝑒 1 1 πœ‹ 6 𝑖
  • D 1 𝑧 = 1 3 𝑒 πœ‹ 6 𝑖

Q2:

What do we need to do to multiply two complex numbers in polar form?

  • Aadd their moduli together and multiply their arguments
  • Badd their moduli together and add their arguments
  • Cmultiply their moduli together and multiply their arguments
  • Dmultiply their moduli together and add their arguments
  • Emultiply their moduli together and subtract their arguments

Q3:

Given that 𝑧 = 2 0 ο€» πœ‹ 2 + 𝑖 πœ‹ 2  1 c o s s i n and 𝑧 = 4 ο€» πœ‹ 6 + 𝑖 πœ‹ 6  2 c o s s i n , find 𝑧 𝑧 1 2 in polar form.

  • A 5 ο€Ό 2 πœ‹ 3 + 𝑖 2 πœ‹ 3  c o s s i n
  • B 8 0 ο€» πœ‹ 3 + 𝑖 πœ‹ 3  c o s s i n
  • C 5 ο€» πœ‹ 2 + 𝑖 πœ‹ 2  c o s s i n
  • D 5 ο€» πœ‹ 3 + 𝑖 πœ‹ 3  c o s s i n
  • E 1 6 ο€» πœ‹ 3 + 𝑖 πœ‹ 3  c o s s i n

Q4:

Given that 𝑧 = ο€Ό 7 πœ‹ 6  + 𝑖 ο€Ό 7 πœ‹ 6  c o s s i n , find 1 𝑧 .

  • A s i n c o s ο€Ό 5 πœ‹ 6  + 𝑖 ο€Ό 5 πœ‹ 6 
  • B c o s s i n ο€Ό 7 πœ‹ 6  + 𝑖 ο€Ό 7 πœ‹ 6 
  • C c o s s i n ο€» πœ‹ 6  + 𝑖 ο€» πœ‹ 6 
  • D c o s s i n ο€Ό 5 πœ‹ 6  + 𝑖 ο€Ό 5 πœ‹ 6 

Q5:

Given that 𝑧 = 2 ο€» πœ‹ 6 + 𝑖 πœ‹ 6  1 c o s s i n and 𝑧 = 1 √ 3 ο€» πœ‹ 3 + 𝑖 πœ‹ 3  2 c o s s i n , find 𝑧 𝑧 1 2 .

  • A 2 √ 3 3 ο€Ό 1 1 πœ‹ 6 + 𝑖 1 1 πœ‹ 6  c o s s i n
  • B ο€Ώ 2 + 1 √ 3  ο€» πœ‹ 2 + 𝑖 πœ‹ 2  c o s s i n
  • C ο€Ώ 2 + 1 √ 3  ο€Ό 1 1 πœ‹ 6 + 𝑖 1 1 πœ‹ 6  c o s s i n
  • D 2 √ 3 3 ο€» πœ‹ 2 + 𝑖 πœ‹ 2  c o s s i n
  • E 2 √ 3 3 ο€» πœ‹ 2 + 𝑖 πœ‹ 2  c o s s i n 2 2

Q6:

Given that 𝑧 = 5 ο€» πœ‹ 3 + 𝑖 πœ‹ 3  1 c o s s i n and 𝑧 = √ 2 ο€Ό 5 πœ‹ 6 + 𝑖 5 πœ‹ 6  2 c o s s i n , find 𝑧 𝑧 1 2 .

  • A 5 √ 2 ο€Ό 3 πœ‹ 2 + 𝑖 3 πœ‹ 2  c o s s i n
  • B ο€» 5 + √ 2  ο€Ό 7 πœ‹ 6 + 𝑖 7 πœ‹ 6  c o s s i n
  • C ο€» 5 + √ 2  ο€Ό 3 πœ‹ 2 + 𝑖 3 πœ‹ 2  c o s s i n
  • D 5 √ 2 ο€Ό 7 πœ‹ 6 + 𝑖 7 πœ‹ 6  c o s s i n
  • E 5 √ 2 ο€Ό 7 πœ‹ 6 + 𝑖 7 πœ‹ 6  c o s s i n 2 2

Q7:

Given that 𝑧 = 1 6 ( 4 5 + 𝑖 4 5 ) 1 ∘ ∘ 2 c o s s i n and 𝑧 = 2 ( βˆ’ 2 8 5 βˆ’ 𝑖 2 8 5 ) 2 ∘ ∘ 2 s i n c o s , find 𝑧 𝑧 1 2 .

  • A 3 2 ( 1 2 0 + 𝑖 1 2 0 ) c o s s i n ∘ ∘
  • B 8 ( 6 0 + 𝑖 6 0 ) c o s s i n ∘ ∘
  • C 3 2 ( 6 0 + 𝑖 6 0 ) c o s s i n ∘ ∘
  • D 8 ( 1 2 0 + 𝑖 1 2 0 ) c o s s i n ∘ ∘
  • E 8 ( 0 + 𝑖 0 ) c o s s i n ∘ ∘

Q8:

Given that , , , and , find .

  • A
  • B
  • C
  • D

Q9:

Given that , , and , where , find .

  • A
  • B
  • C
  • D
  • E

Q10:

Given that 𝑧 = 4 ( 4 5 + 𝑖 4 5 ) 1 ∘ ∘ c o s s i n and 𝑧 = 6 ( 9 0 + 𝑖 9 0 ) 2 ∘ ∘ c o s s i n , find the exponential form of 𝑧 𝑧 2 1 .

  • A 2 3 𝑒 πœ‹ 4 𝑖
  • B 2 3 𝑒 7 πœ‹ 4 𝑖
  • C 4 𝑒 7 πœ‹ 4 𝑖
  • D 3 2 𝑒 πœ‹ 4 𝑖
  • E 6 𝑒 7 πœ‹ 4 𝑖

Q11:

Given that 𝑧 = 1 2 βˆ’ √ 3 2 𝑖 1 and 𝑧 = 2 √ 3 + 2 𝑖 2 , find 𝑧 𝑧 1 2 , giving your answer in exponential form.

  • A 𝑧 𝑧 = 4 𝑒 1 2 𝑖 3 πœ‹ 2
  • B 𝑧 𝑧 = 1 4 𝑒 1 2 𝑖 5 πœ‹ 3
  • C 𝑧 𝑧 = 𝑒 1 2 𝑖 3 πœ‹ 2
  • D 𝑧 𝑧 = 1 4 𝑒 1 2 𝑖 3 πœ‹ 2
  • E 𝑧 𝑧 = 1 4 𝑒 1 2 𝑖 πœ‹ 6

Q12:

If 𝑍 = 7 ( πœƒ + 𝑖 πœƒ ) 1 1 1 c o s s i n , 𝑍 = 1 6 ( πœƒ + 𝑖 πœƒ ) 2 2 2 c o s s i n , and πœƒ + πœƒ = πœ‹ 1 2 , then what is 𝑍 𝑍 1 2 ?

  • A 1 1 2 𝑖
  • B112
  • C βˆ’ 1 1 2 𝑖
  • D βˆ’ 1 1 2

Q13:

Simplify 4 ( 9 0 + 𝑖 9 0 ) Γ— 5 ( 8 0 + 𝑖 8 0 ) Γ— 4 ( 4 5 + 𝑖 4 5 ) c o s s i n c o s s i n c o s s i n ∘ ∘ ∘ ∘ ∘ ∘ , giving your answer in trigonometric form.

  • A 8 0 ( 1 2 5 + 𝑖 1 2 5 ) c o s s i n ∘ ∘
  • B 1 3 ( 2 1 5 + 𝑖 2 1 5 ) c o s s i n ∘ ∘
  • C 8 0 ( 2 1 5 + 𝑖 2 1 5 ) s i n c o s ∘ ∘
  • D 8 0 ( 2 1 5 + 𝑖 2 1 5 ) c o s s i n ∘ ∘

Q14:

Given that and , find .

  • A
  • B
  • C
  • D
  • E

Q15:

Given that and , where , determine the trigonometric form of .

  • A
  • B
  • C
  • D
  • E

Q16:

Given that 𝑧 = 2 ( 5 π‘Ž + 𝑖 5 π‘Ž ) 1 c o s s i n and 𝑧 = 4 ( 3 π‘Ž βˆ’ 𝑖 3 π‘Ž ) 2 s i n c o s , determine 𝑧 𝑧 1 2 .

  • A 8 ( ( 2 7 0 βˆ’ 8 π‘Ž ) + 𝑖 ( 2 7 0 βˆ’ 8 π‘Ž ) ) c o s s i n ∘ ∘
  • B 6 ( ( 9 0 + 8 π‘Ž ) + 𝑖 ( 9 0 + 8 π‘Ž ) ) c o s s i n ∘ ∘
  • C 6 ( ( 9 0 βˆ’ 8 π‘Ž ) + 𝑖 ( 9 0 βˆ’ 8 π‘Ž ) ) c o s s i n ∘ ∘
  • D 8 ( ( 2 7 0 + 8 π‘Ž ) + 𝑖 ( 2 7 0 + 8 π‘Ž ) ) c o s s i n ∘ ∘
  • E 8 ( 8 π‘Ž + 𝑖 8 π‘Ž ) c o s s i n

Q17:

If and , is it true that ?

  • Ayes
  • Bno

Q18:

Given that 𝑧 = 5 ο€Ό 5 πœ‹ 6 + 𝑖 5 πœ‹ 6  1 c o s s i n and 𝑧 = 4 ( 1 8 0 + 𝑖 1 8 0 ) 2 ∘ ∘ c o s s i n , determine 𝑧 𝑧 1 2 .

  • A 2 0 ( 3 0 + 𝑖 3 0 ) c o s s i n ∘ ∘
  • B 9 ( 3 3 0 + 𝑖 3 3 0 ) c o s s i n ∘ ∘
  • C 9 ( 3 3 0 βˆ’ 𝑖 3 3 0 ) c o s s i n ∘ ∘
  • D 2 0 ( 3 3 0 + 𝑖 3 3 0 ) c o s s i n ∘ ∘
  • E 2 0 ο€Ί 3 3 0 + 𝑖 3 3 0  c o s s i n 2 ∘ 2 ∘

Q19:

Given that 𝑧 = 2 ( ( 5 π‘Ž βˆ’ 2 𝑏 ) + 𝑖 ( 5 π‘Ž βˆ’ 2 𝑏 ) ) 1 c o s s i n and 𝑧 = 4 ( ( 4 π‘Ž βˆ’ 3 𝑏 ) + 𝑖 ( 4 π‘Ž βˆ’ 3 𝑏 ) ) 2 c o s s i n , find 𝑧 𝑧 1 2 .

  • A 8 ( ( 2 0 π‘Ž + 6 𝑏 ) + 𝑖 ( 2 0 π‘Ž + 6 𝑏 ) ) c o s s i n
  • B 6 ( ( 9 π‘Ž βˆ’ 5 𝑏 ) + 𝑖 ( 9 π‘Ž βˆ’ 5 𝑏 ) ) c o s s i n
  • C 6 ( ( 2 0 π‘Ž + 6 𝑏 ) + 𝑖 ( 2 0 π‘Ž + 6 𝑏 ) ) c o s s i n
  • D 8 ( ( 9 π‘Ž βˆ’ 5 𝑏 ) + 𝑖 ( 9 π‘Ž βˆ’ 5 𝑏 ) ) c o s s i n
  • E 1 2 ( ( π‘Ž + 𝑏 ) + 𝑖 ( π‘Ž + 𝑏 ) ) c o s s i n

Q20:

Given that 𝑧 = βˆ’ 1 5 0 βˆ’ 𝑖 1 5 0 1 ∘ ∘ s i n c o s and that 𝑧 = 2 ( 1 2 0 βˆ’ 𝑖 1 2 0 ) 2 ∘ ∘ s i n c o s , find 𝑧 𝑧 1 2 .

  • A 2 ( 2 7 0 + 𝑖 2 7 0 ) c o s s i n ∘ ∘
  • B 3 ( 1 5 0 + 𝑖 1 5 0 ) c o s s i n ∘ ∘
  • C 3 ( 2 7 0 + 𝑖 2 7 0 ) c o s s i n ∘ ∘
  • D 2 ( 1 5 0 + 𝑖 1 5 0 ) c o s s i n ∘ ∘

Q21:

Given that 𝑧 = 7 ( 3 1 5 + 𝑖 3 1 5 ) s i n c o s ∘ ∘ , find 𝑧 2 , giving your answer in exponential form.

  • A 4 9 𝑒 7 πœ‹ 4 𝑖
  • B 4 9 𝑒 3 πœ‹ 4 𝑖
  • C 7 𝑒 3 πœ‹ 2 𝑖
  • D 4 9 𝑒 3 πœ‹ 2 𝑖
  • E 1 4 𝑒 3 πœ‹ 2 𝑖

Q22:

Given that 𝑧 = 3 √ 2 ( 2 2 5 βˆ’ 𝑖 2 2 5 ) c o s s i n ∘ ∘ , find 𝑧 2 , giving your answer in exponential form.

  • A 3 √ 2 𝑒 3 πœ‹ 2 𝑖
  • B 1 8 𝑒 3 πœ‹ 4 𝑖
  • C 6 √ 2 𝑒 3 πœ‹ 2 𝑖
  • D 1 8 𝑒 3 πœ‹ 2 𝑖

Q23:

Given that 𝑧 = 2 ( 9 0 βˆ’ 𝑖 9 0 ) 1 ∘ ∘ c o s s i n and 𝑧 = 4 ( 3 0 + 𝑖 3 0 ) 2 ∘ ∘ s i n c o s , find 𝑧 𝑧 1 2 , giving your answer in exponential form.

  • A 𝑧 𝑧 = 8 𝑒 1 2 𝑖 5 πœ‹ 3
  • B 𝑧 𝑧 = 8 𝑒 1 2 𝑖 2 πœ‹ 3
  • C 𝑧 𝑧 = 8 𝑒 1 2 𝑖 5 πœ‹ 6
  • D 𝑧 𝑧 = 8 𝑒 1 2 𝑖 1 1 πœ‹ 6
  • E 𝑧 𝑧 = 6 𝑒 1 2 𝑖 1 1 πœ‹ 6

Q24:

If 𝑧 = 2 1 0 + 𝑖 2 1 0 1 ∘ ∘ c o s s i n , 𝑧 = 3 ( 1 3 5 + 𝑖 1 3 5 ) 2 ∘ ∘ c o s s i n , and 𝑧 = 4 ( 1 3 5 + 𝑖 1 3 5 ) 3 ∘ ∘ c o s s i n , what is the exponential form of ( 𝑧 𝑧 𝑧 ) 1 2 3 4 ?

  • A 𝑒 2 πœ‹ 3 𝑖
  • B 1 2 𝑒 2 πœ‹ 3 𝑖
  • C 2 0 7 3 6 𝑒 5 πœ‹ 3 𝑖
  • D 2 0 7 3 6 𝑒 2 πœ‹ 3 𝑖

Q25:

Given that 𝑧 = 2 √ 3 ( 2 4 0 + 𝑖 2 4 0 ) c o s s i n ∘ ∘ , find 𝑧 2 in exponential form.

  • A 𝑧 = 2 √ 3 𝑒 2 𝑖 2 πœ‹ 3
  • B 𝑧 = 1 2 𝑒 2 𝑖 4 πœ‹ 3
  • C 𝑧 = 4 √ 3 𝑒 2 𝑖 2 πœ‹ 3
  • D 𝑧 = 1 2 𝑒 2 𝑖 2 πœ‹ 3
  • E 𝑧 = 1 2 𝑒 2 𝑖 7 πœ‹ 6